Domestic Wastewater Treatment to Control River Pollution in Sungai Pinang, Samarinda, East Kalimantan - Suhartono, Eko; Erlena, Erlena; Sekartaji, Hapsari Lintang; Putera, Gusti Muhammad Perdana; Thalib, Iskandar; Syauqiah, Isna; Hafifah, Ifa; Trang, Ha Thi Thu (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Filtration is a method for controlling water pollution. This study aimed to engineer a filtration system using a combination of Melaleuca cajuputi (galam) wood charcoal and zeolite to process domestic wastewater. The research focused on domestic wastewater from Sungai Pinang Village, Samarinda, East Kalimantan, an area with significant water pollution issues. The samples were divided into three groups, each containing zeolite and galam wood charcoal in different ratios: Group 1 (1:1), Group 2 (1:2), and Group 3 (2:1). Each sample was exposed to contact times of 30, 60, and 90 minutes. Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Ammonia (NH3), and pH were measured for each treatment group at each contact time. Results showed that prolonged contact with the filtration method significantly reduced all parameters except pH (P<0.05). Each treatment combination did not significantly reduce all parameters except pH (P>0.05). Group 2 was found to be the most effective in improving water quality. In conclusion, this study demonstrates that the filtration method can reduce pollutant levels, with the combination of galam wood charcoal and zeolite in a 2:1 ratio being the most effective.